2013
DOI: 10.1167/iovs.12-10066
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Heritability of Peripheral Eye Length in Chinese Children and Adolescents: The Guangzhou Twin Eye Study

Abstract: Additive genetic effects had a substantial influence on phenotypic variation in PEL and RPEL, suggesting genetic rather than environmental factors play a major role in determining eye shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Retinal shape can be estimated by indirect optical methods that are based on peripheral refraction [11][12][13], partial coherence interferometry [14][15][16][17][18][19][20][21][22][23][24] and optical coherence tomography [25,26]. However such methods rely on assumptions concerning shape and refractive index distribution through the lens and other structures within the eye, in order to convert optical path lengths into geometrical dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal shape can be estimated by indirect optical methods that are based on peripheral refraction [11][12][13], partial coherence interferometry [14][15][16][17][18][19][20][21][22][23][24] and optical coherence tomography [25,26]. However such methods rely on assumptions concerning shape and refractive index distribution through the lens and other structures within the eye, in order to convert optical path lengths into geometrical dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the relationship between retinal shape and myopia, retinal shape has been inferred from peripheral refraction and peripheral eye length measurements . For example, positive relative peripheral refraction and negative relative peripheral eye length are considered to be associated with a ‘prolate’ shape (flattening away from the vertex) of the retina.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, a genetic factor has been emphasized because of the observation that myopic parents give birth to myopic children. In fact, heritability was confirmed statistically in multiple studies with monozygotic and heterozygotic twins . Studies of 12‐year‐old Australian children showed that prevalence of myopia increases with the number of myopic parents.…”
Section: Genetics Of Myopiamentioning
confidence: 82%